Lagenorhynchus albirostris - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Lagenorhynchus albirostris (Gray, 1846). Ann. Mag. Nat. Hist., 17:84. TYPE LOCALITY: U.K., England, Norfolk, Great Yarmouth. DISTRIBUTION: Cold temperate to subarctic waters of the North Atlantic, south to Newfoundland and Portugal. PROTECTED STATUS: CITES - Appendix II as Order Cetacea. ISIS NUMBER: 5301411002012002001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Cetacea, pp. 290-304 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 293, DOI: 10.5281/zenodo.7352983